Impact of YTHDF1 gene polymorphisms on Wilms tumor susceptibility: A five‐center case‐control study. Issue 8 (21st June 2021) - Liu, Yanfei; Lin, Huiran; Hua, Rui‐Xi; Zhang, Jiao; Cheng, Jiwen; Li, Suhong; Zhou, Haixia; Zhuo, Zhenjian; Bian, Jun
Abstract: Background: Wilms tumor is the most frequent renal malignancy in children. YTHDF1 is associated with the development of several kinds of cancers, yet whether common variants of the YTHDF1  gene influence Wilms tumor risk is unknown. We present, here, a hospital‐based case‐control study specifically designed to investigate the role of YTHDF1  genetic variants on Wilms tumor. Methods: We successfully genotyped samples of 408 Wilms tumor cases and 1198 controls which were collected from five hospitals across China. The unconditional logistic regression was adopted to analyze the contributions of YTHDF1  gene single nucleotide polymorphisms (SNPs) to the risk of Wilms tumor. The odds ratio (OR) and 95% confidence interval (CI) were generated to evaluate the conferring risk of YTHDF1  gene SNPs (rs6011668 C>T, rs6090311 A>G). Results: Neither of the two SNPs could contribute to the risk of Wilms tumor. A negative association was also detected in the combined effects of protective genotypes on Wilms tumor risk. The stratification analysis revealed that compared with those with CC genotype, rs6011668 CT/TT genotype was associated with increased Wilms tumor risk in those ≤18 months (OR = 1.54, 95% CI = 1.02–2.30, p  = 0.038), and with decreased Wilms tumor risk in those >18 months (OR = 0.70, 95% CI = 0.50–0.97, p  = 0.034). Conclusion: Our present work sheds some light on the potential role of YTHDF1  gene polymorphisms on Wilms tumor risk. Abstract : YTHDF1 gene SNPs (rs6011668 C>T, rs6090311 A>G) could not contribute to the risk of Wilms tumor. A negative association was also detected in the combined effects of protective genotypes on Wilms tumor risk. The stratification analysis revealed that compared with those with CC genotype, rs6011668 CT/TT genotype was associated with increased Wilms tumor risk in those ≤18 months, and with decreased Wilms tumor risk in those >18 months.